2010
DOI: 10.1074/jbc.m110.171637
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Localization of a Lipase-like Acyltransferase in Phenylpropanoid Metabolism of Tomato (Solanum lycopersicum)

Abstract: We have isolated an enzyme classified as chlorogenate: glucarate caffeoyltransferase (CGT) from seedlings of tomato (Solanum lycopersicum) that catalyzes the formation of caffeoylglucarate and caffeoylgalactarate using chlorogenate (5-O-caffeoylquinate) as acyl donor. Peptide sequences obtained by trypsin digestion and spectrometric sequencing were used to isolate the SlCGT cDNA encoding a protein of 380 amino acids with a putative targeting signal of 24 amino acids indicating an entry of the SlCGT into the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 55 publications
(50 reference statements)
3
32
0
Order By: Relevance
“…A biological role of GDSL-lipases in cutin deposition is in agreement with previous data showing that these proteins are localized to the apoplastic space of seedlings (Takahashi et al, 2010;Teutschbein et al, 2010) or to the epidermis of leaves and fruits (Reina et al, 2007;Matas et al, 2010;Yeats et al, 2010). Although the structure and composition of cutin were not characterized, the cosilencing of two Arabidopsis GDSL-lipases led to severe floral organ fusion and major changes in the architecture of epidermis cells .…”
Section: Gdsl1 Is An Extracellular Protein Primarily Involved In Cutisupporting
confidence: 77%
See 1 more Smart Citation
“…A biological role of GDSL-lipases in cutin deposition is in agreement with previous data showing that these proteins are localized to the apoplastic space of seedlings (Takahashi et al, 2010;Teutschbein et al, 2010) or to the epidermis of leaves and fruits (Reina et al, 2007;Matas et al, 2010;Yeats et al, 2010). Although the structure and composition of cutin were not characterized, the cosilencing of two Arabidopsis GDSL-lipases led to severe floral organ fusion and major changes in the architecture of epidermis cells .…”
Section: Gdsl1 Is An Extracellular Protein Primarily Involved In Cutisupporting
confidence: 77%
“…In support of such an assertion, one can mention that the maize (Zea mays) acetylcholine esterase, Brassica napus sinapine esterase, and the chlorogenate:glucarate caffeoyltransferase of tomato seedlings share the same GDSL motif and the five conserved domains with GDSL1 (Sagane et al, 2005;Clauss et al, 2008;Teutschbein et al, 2010).…”
Section: Gdsl1 Is An Extracellular Protein Primarily Involved In Cutimentioning
confidence: 98%
“…In respect of this enzyme, mutations of the catalytic-triad serine in Block I, as well as of the aspartate and histidine in Block V had only a small impact on the activity. 7) However, this may not be the case for the pyrethrin-forming acyltransferase activity of TcGLIP, since we have observed that the S40A mutation eliminated the activity. 4) We prepared in this present study MBP-fused and MBP-free TcGLIPs to examine the effects of MBP on the acyltransferase activity.…”
Section: )mentioning
confidence: 82%
“…The D328A and H331A mutations, and also even the S27A mutation, only had a small impact on the glucarate caffeoyltransferase activity. 7) In the case of TcGLIP, however, mutations of the corresponding amino acids markedly reduced the pyrethrin-synthesizing acyltransferase activity. The results and our previous observation of the S40A mutation-induced complete loss of hydrolase activity 4) appear to suggest that the acyltransferase and hydrolase activities of TcGLIP shared a common mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation